2020
DOI: 10.1002/mds3.10154
|View full text |Cite
|
Sign up to set email alerts
|

Stretchable triboelectric sensor for measurement of the forearm muscles movements and fingers motion for Parkinson's disease assessment and assisting technologies

Abstract: Parkinson's disease (PD) is a degenerative, neurological disease that causes motor dysfunctions on the patient. Currently, the symptoms and progression of the disease are assessed by physicians who diagnose through careful observation, according to the Movement Disorder Society (MDS)-sponsored Revision of the Unified Parkinson's Disease Rating Scale (UPDRS). In this manuscript, we report a portable sensor device based on a flexible Triboelectric Nanogenerator (TENG) formed from a dielectric material with a siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…[212] For instance, since Parkinson's disease causes autonomic dysfunction, it is possible to diagnose it by detecting human motion with wearable physical sensors. [213] Real-time monitoring of physical biosignals without being separated from the human body is necessary in order to detect human movement and use that information to diagnose diseases. However, it is challenging to fix the sensor to the body since the human body moves constantly, and secretions, such as perspiration, are produced continuously.…”
Section: Trending Noveltymentioning
confidence: 99%
“…[212] For instance, since Parkinson's disease causes autonomic dysfunction, it is possible to diagnose it by detecting human motion with wearable physical sensors. [213] Real-time monitoring of physical biosignals without being separated from the human body is necessary in order to detect human movement and use that information to diagnose diseases. However, it is challenging to fix the sensor to the body since the human body moves constantly, and secretions, such as perspiration, are produced continuously.…”
Section: Trending Noveltymentioning
confidence: 99%
“…The individual needs of different patients can be met by changing the appearance structure. At the same time, Yuce et al developed a self-powered TENG for diagnosis of Parkinson’s disease [ 65 ]. This nanogenerator was made of flexible materials, and through customization was able to meet the need for patients to be able to wear it for a long time.…”
Section: Real-time Medical Diagnostic Equipmentmentioning
confidence: 99%
“…Further work by Anaya et al [ 103 ] has shown the development of a portable TENG-based sensor to monitor the movement of forearm muscles and tendons for people suffering from Parkinson’s disease. When the hand or fingers extend or flex, the gap between the dielectric polymer (Ecoflex™, 4 × 3.5 cm) and the conductor (Aluminum, 2 × 3 cm) deposited on a PCB changes, generating a voltage due to triboelectric contact.…”
Section: Current State Of the Art Of Self-powered Poc Sensors And mentioning
confidence: 99%